1994
DOI: 10.1042/bj3030021
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of glycogen synthase kinase-3 by insulin or insulin-like growth factor 1 in the rat skeletal muscle cell line L6 is blocked by wortmannin, but not by rapamycin: evidence that wortmannin blocks activation of the mitogen-activated protein kinase pathway in L6 cells between Ras and Raf

Abstract: Glycogen synthase kinase-3 (GSK3) is inactivated in vitro by p70 S6 kinase or MAP kinase-activated protein kinase-1 beta (MAPKAP kinase-1 beta; also known as Rsk-2). Here we show that GSK3 isoforms are inhibited by 40% within minutes after stimulation of the rat skeletal-muscle cell line L6 with insulin-like growth factor-1 (IGF-1) or insulin. GSK3 was similarly inhibited in rabbit skeletal muscle after an intravenous injection of insulin. Inhibition resulted from increased phosphorylation of GSK3, probably at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
210
2
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 454 publications
(228 citation statements)
references
References 43 publications
14
210
2
2
Order By: Relevance
“…Distinct experimental approaches have led to the conclusion that PI 3-kinase is necessary for insulin-stimulated GLUT4 translocation [38][39][40][41][42][43][44]. Evidence from other sources has also demonstrated a correlation between PI 3-kinase activity and glycogen metabolism [45,46]. Thus, it is reasonable to speculate that the IRS-1/PI 3-kinase pathway may be linked to the activation of glucose transport in muscle and glycogen synthesis in liver and muscle, and that a reduction in this association in pregnancy may have a role in the insulin resistance in liver and muscle of pregnant rats.…”
Section: Discussionmentioning
confidence: 99%
“…Distinct experimental approaches have led to the conclusion that PI 3-kinase is necessary for insulin-stimulated GLUT4 translocation [38][39][40][41][42][43][44]. Evidence from other sources has also demonstrated a correlation between PI 3-kinase activity and glycogen metabolism [45,46]. Thus, it is reasonable to speculate that the IRS-1/PI 3-kinase pathway may be linked to the activation of glucose transport in muscle and glycogen synthesis in liver and muscle, and that a reduction in this association in pregnancy may have a role in the insulin resistance in liver and muscle of pregnant rats.…”
Section: Discussionmentioning
confidence: 99%
“…However, SB 203580 does not induce any activation of MKK1 or MAPK2 (Figure 2). Moreover, incubation of Swiss 3T3 cells with PD 98059 (50 mM), which prevents the activation of MAPK2 by EGF (Figure 2 The activation of c-Raf by di erent agonists can result from the stimulation of several signalling pathways, including the activation of protein kinase C (PKC) (Morrison and Cutler, 1997) or phosphatidylinositide (PtdIns) 3-kinase (Cross et al, 1994). However, c-Raf activation is una ected by Ro 318220 (Figure 4), an inhibitor of PKC and some other protein kinases (Alessi, 1997), under conditions where the PMA-induced activation of MAPK2 measured in the same cells was decreased by 85%.…”
Section: Mechanism Of Activation Of C-raf By Sb 203580mentioning
confidence: 99%
“…However, it is now clear that Ras also regulates the activity of a number of other signaling pathways through activation of proteins such as phosphatidylinositol 3-kinase (Pl3-K) and RalGDS (4,55). There is much interest in the cross talk that exists between these different, parallel Ras pathways, and in some but not all cell types, inhibition of Pl3-K that leads to suppression of ERK has been shown (8,16,24,56). In different studies, Pl3-K has been shown to regulate ERK activation at the level of Ras or at the level of Raf-1 (7,8,27,56).…”
mentioning
confidence: 99%
“…There is much interest in the cross talk that exists between these different, parallel Ras pathways, and in some but not all cell types, inhibition of Pl3-K that leads to suppression of ERK has been shown (8,16,24,56). In different studies, Pl3-K has been shown to regulate ERK activation at the level of Ras or at the level of Raf-1 (7,8,27,56). More recently, it was suggested that Pl3-K regulates Raf-1 by activating protein kinases that can phosphorylate Raf-1 directly.…”
mentioning
confidence: 99%